Epidemiology of Nontuberculous Mycobacteriosis - Adjemian, Jennifer; Daniel-Wayman, Shelby; Ricotta, Emily; Prevots, D. Rebecca (Seminars in Respiratory and Critical Care Medicine, 2018)
Annual prevalence estimates for pulmonary nontuberculous mycobacterial (PNTM) disease in the contiguous United States range from 1.4 to 13.9 per 100,000 persons, while one study found an annual prevalence of up to 44 per 100,000 persons in Hawaii. PNTM prevalence varies by region, sex, and race/ethnicity, with higher prevalence among women and persons of Asian ancestry, as well as in the Southern United States and Hawaii. Studies consistently indicate that PNTM prevalence is increasing, with estimates ranging from 2.5 to 8% per year. Most PNTM disease is associated with Mycobacterium avium complex (MAC), although the proportion of disease attributed to MAC varies by region. Host factors identified as influencing disease risk include structural lung disease, immunomodulatory medication, as well as variants in connective tissue, mucociliary clearance, and immune genes. Environmental variables including measures of atmospheric moisture and concentrations of certain soil factors have also been shown to correlate with higher PNTM prevalence. Prevalence of extrapulmonary NTM disease is lower, stable, and associated with different risk factors, including primary immune deficiencies or HIV infection.
Keywords: epidemiology; nontuberculous mycobacteria; pulmonary disease